2013
DOI: 10.1037/a0033079
|View full text |Cite
|
Sign up to set email alerts
|

Does low birth weight share common genetic or environmental risk with childhood disruptive disorders?

Abstract: Although advances in neonatal care over the past century have resulted in increased rates of survival among at-risk births, including infants with low birth weight, we have much to learn about the psychological outcomes in this population. In particular, although it appears that there is growing evidence that low birth weight may be associated with an increased risk for Attention-Deficit/Hyperactive Disorder (ADHD) symptoms in childhood, few studies have examined birth weight as a risk factor for disruptive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 67 publications
5
31
0
Order By: Relevance
“…Though some previous research has reported null findings (1, 5, 18), the current results build on previous co-twin control (2, 4, 1012) and epidemiological study findings (3). The associations between birth weight and psychotic or bipolar disorder were also independent of shared familial confounds and statistical covariates, although the magnitudes of association were attenuated in fixed effects models.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Though some previous research has reported null findings (1, 5, 18), the current results build on previous co-twin control (2, 4, 1012) and epidemiological study findings (3). The associations between birth weight and psychotic or bipolar disorder were also independent of shared familial confounds and statistical covariates, although the magnitudes of association were attenuated in fixed effects models.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, it was not possible to classify ADHD cases according to subtype (i.e., combined, primarily hyperactive-impulsive and primarily inattentive type), since these were not recorded across the registers using the ICD. Offspring had to have been at least 12 years old to receive any of the following disorders: (3) psychotic or bipolar disorder was defined as first inpatient hospitalization for schizophrenia, bipolar disorder, or another non-organic psychotic disorder according to ICD-8, -9, and -10 criteria (29); (4) substance use problem was defined as first inpatient hospitalization for a primary or secondary diagnosis of alcohol or any other non-nicotine substance use disorder (30); (5) age at suicide attempt was gathered using inpatient hospitalization for a primary or secondary diagnosis (31); and (6) criminality was indicated by the first occurrence of any criminal conviction from age 15 years, the age of legal responsibility in Sweden (32). We chose not to examine broadly defined affective disorder because inpatient hospitalization for that diagnosis may indicate the presence of co-occurring suicidality or psychosis, and we had access to validated indicators of these associated possible outcomes (29, 31).…”
Section: Methodsmentioning
confidence: 99%
“…The recommendation based on the present data would be to model continuous rather than dichotomous measures in testing hypotheses regarding the association between perinatal events and offspring development. In fact, comparing the effect sizes for continuous birthweight and low birthweight (i.e., < 2500 grams) on inattention and behavior problems in the Tennessee Twin Study resulted in the authors concluding that the continuous term for birthweight was a stronger predictor than the categorical variable [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Yet, studies that utilize this methodology have reported inconsistent findings. While some studies have reported no associations between maternal report of birth complications, and low birthweight and offspring neurodevelopmental problems [10,11], others have shown that maternal recall of birth events predicts youth behavior problems [12,13,14]. For example, in two child epidemiologic studies, maternal recall of birthweight was unrelated to offspring behavior problems [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This allows for the possibility that birth weight and ADHD share a common genetic liability. Twin studies, however, demonstrate that prenatal environmental factors, rather than shared genetic factors, largely account for the relationship between birth weight and ADHD symptoms [Lehn et al, 2007;Groen-Blokhuis et al, 2011;Ficks et al, 2013;Sharp et al, 2003] or externalizing behavior [van Os et al, 2001;Wichers et al, 2002]. This suggests that environmental determinants of lower birth weight contribute to the development of ADHD.…”
Section: Introductionmentioning
confidence: 99%